KOMUNITAS PUSTAKAWAN MENULIS (Upaya Menyebarluaskan dan Melestarikan Pengetahuan) - Tri Hardiningtyas (Central Library of Universitas Sebelas Maret, 2019)
The subject matter that will be discussed on the writing competence librarians ascontributors to and preservation of information as knowledge. This paper to explore the writing competence of librarians in contributing to the wealth of knowledge in historical knowledge. Writing of competence librarians can be done by following a community librarian wrote. This work by using the method of literature study conducted by way of data describing the authorship librarian at the time of filing the number of credits that accompanied grain authorship professional development activities. The results showed that the writing competence librarian yet provide maximum results as a contributor in the dissemination and preservation of information. The work of the librarians should be explored and pursued through the establishment of community to be able to write. Written works especially librarians who are ready to share the results of writing published in a sense as an effort dissemination and preservation ofinformation. The conclusions from this study that the competence to write librarians can play a role as contributing of knowledge, writing librarians same with other professions, yet the number of papers produced by the librarian because of a lack of effort to improve the writing competence librarians continue to be more exercise superior and capable of being the biggest contributor to the treasures of knowledge.Keywords: librarians writing; competency of writing; library; librarian